Novel Targets for Therapy of Renal Fibrosis. (September 2019) - Prakoura, Niki; Hadchouel, Juliette; Chatziantoniou, Christos
Renal fibrosis is an important component of chronic kidney disease, an incurable pathology with increasing prevalence worldwide. With a lack of available therapeutic options, end-stage renal disease is currently treated with renal replacement therapy through dialysis or transplantation. In recent years, many efforts have been made to identify novel targets for therapy of renal diseases, with special focus on the characterization of unknown mediators and pathways participating in renal fibrosis development. Using experimental models of renal disease and patient biopsies, we identified four novel mediators of renal fibrosis with potential to constitute future therapeutic targets against kidney disease: discoidin domain receptor 1, periostin, connexin 43, and cannabinoid receptor 1. The four candidates were highly upregulated in different models of renal disease and were localized at the sites of injury. Subsequent studies showed that they are centrally involved in the underlying mechanisms of renal fibrosis progression. Interestingly, inhibition of either of these proteins by different strategies, including gene deletion, antisense administration, or specific blockers, delayed the progression of renal disease and preserved renal structure and function, even when the inhibition started after initiation of the disease. This review will summarize the current findings on these candidates emphasizing on their potential to constitute future targets of therapy: